Hermeneutics, Retranslation and Paratext: a Case Study of Seamus Heaney’s Preface to His Retranslation of „Beowulf” - Saki, Mohamed (Research in Language, 2021)
This paper sets to analyse the hermeneutical process of highlighting at work in the preface written by the North Irish poet Seamus Heaney to his retranslations of Beowulf (1999). My analysis takes into account the generic identity of the preface by considering it as a textual subgenre where the translator becomes a metatranslator to voice herself out of invisibility, engages in a (self-reflexive) hermeneutical analysis and “justification” by commenting on the choice of the translated work and their translation choices. The analysis is carried out with the help of two concepts elaborated by Gadamer: situatedness and self-understanding to show how Seamus Heaney fuses different horizons in the process of his retranslation.